Best Paper Selection (Yearbook of Medical Informatics, 2019)
Jing B, Xie P Xing E. On the automatic generation of medical imaging reports. Proc of ACL 2018. Melbourne, Australia; 2018. p. 2577-86 https://www.aclweb.org/anthology/P18-1240Moradi M. CIBS: A biomedical text summarizer using topic-based sentence clustering J Biomed Inform 2018;88:53-61 https://www.sciencedirect.com/science/article/pii/S1532046418302156?via%3Dihub